Thin, soft, wearable system for continuous wireless monitoring of artery blood pressure - Li, Jian; Jia, Huiling; Zhou, Jingkun; Huang, Xingcan; Xu, Long; Jia, Shengxin; Gao, Zhan; Yao, Kuanming; Li, Dengfeng; Zhang, Binbin; Liu, Yiming; Huang, Ya; et al. (Nature communications, 2023)
Continuous monitoring of arterial blood pressure (BP) outside of a clinical setting is crucial for preventing and diagnosing hypertension related diseases. However, current continuous BP monitoring instruments suffer from either bulky systems or poor user-device interfacial performance, hampering their applications in continuous BP monitoring. Here, we report a thin, soft, miniaturized system (TSMS) that combines a conformal piezoelectric sensor array, an active pressure adaptation unit, a signal processing module, and an advanced machine learning method, to allow real wearable, continuous wireless monitoring of ambulatory artery BP. By optimizing the materials selection, control/sampling strategy, and system integration, the TSMS exhibits improved interfacial performance while maintaining Grade A level measurement accuracy. Initial trials on 87 volunteers and clinical tracking of two hypertension individuals prove the capability of the TSMS as a reliable BP measurement product, and its feasibility and practical usability in precise BP control and personalized diagnosis schemes development. Continuous monitoring of arterial blood pressure is limited by bulky connecting systems and poor interfacial contact. Here, Li et al. report a wearable thin, soft, miniaturized system that integrates sensing, active pressure adaptation, and signal processing for improved performance and accuracy.